PENGARUH LATIHAN TEHNIK MENEMBAK KE GAWANG /SHOOTING TERHADAP HASIL KETERAMPILAN SHOOTING PADA TIM FUTSAL PUTRI ACCASIA KOTA PEKANBARU - Harisna, Yolla; Zainur, Zainur; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was conducted to determine whether there are effects of exercise shot to goalkeeper "Instep Drive" Against ability Shooting At Accasia Women's Futsal Team Pekanbaru, so that at the time of attack patterns players are able to create more goals into the opponent's goal and can to win the game. The problem in this research that the ability of the athlete shooting Accasia Women's Futsal Team Pekanbaru is still lacking, it is seen from the various trials and friendly matches or official and this is one of the causes of the defeat. This type of research is a kind of research experiments to see the effects of this form of exercise. The purpose of this study is to look at the effects of exercise shots on goal (Instep drive) on the ability of shooting at a Accasia Women's Futsal Team Pekanbaru. The population in this study is the team Accasia Women's Futsal Pekanbaru totaling 16 people. A sampling technique that by using total sampling, where the total population sampled. Data collection techniques derived from the pre-test and post test. Instrument in this study using Test Shooting / Kicking the ball to Goal (Shooting) as a tool to measure the accuracy of shooting. Analyses were performed using t-test. based on data analysis and discussion, as evidenced by Thitung amounted to 3,828 and 1,764 Ttabel. Means Thitung>Ttabel. At some level ɑ = 0.05. It can be concluded that there is significant influence of practice shots on goal against the shooting ability on the Accasia Women's Futsal Team PekanbaruKey Words: Shots On Goal (Shooting), Shooting Ability, Futsal.